2020
DOI: 10.1001/jama.2020.1906
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Dapagliflozin on Worsening Heart Failure and Cardiovascular Death in Patients With Heart Failure With and Without Diabetes

Abstract: IMPORTANCE Additional treatments are needed for heart failure with reduced ejection fraction (HFrEF). Sodium-glucose cotransporter 2 (SGLT2) inhibitors may be an effective treatment for patients with HFrEF, even those without diabetes. OBJECTIVE To evaluate the effects of dapagliflozin in patients with HFrEF with and without diabetes. DESIGN, SETTING, AND PARTICIPANTS Exploratory analysis of a phase 3 randomized trial conducted at 410 sites in 20 countries. Patients with New York Heart Association classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
378
1
28

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 402 publications
(424 citation statements)
references
References 36 publications
17
378
1
28
Order By: Relevance
“…However, the hypothesis that SGLT-2i might be an effective treatment for a broad range of patients with heart failure, including those with preserved ejection fraction (HFpEF), remains mysterious. Besides, trials assessing the effect of SGLT-2 inhibitors on cardiovascular outcomes may have different scales of effects on clinical outcomes [9][10][11][12][13]. Consistent with the results of the DAPA-HA trial, the CANVAS Program [10] found that canagli ozin signi cantly reduced the risk of cardiovascular death or hospitalization for heart failure in patients with HF concomitant with T2DM.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…However, the hypothesis that SGLT-2i might be an effective treatment for a broad range of patients with heart failure, including those with preserved ejection fraction (HFpEF), remains mysterious. Besides, trials assessing the effect of SGLT-2 inhibitors on cardiovascular outcomes may have different scales of effects on clinical outcomes [9][10][11][12][13]. Consistent with the results of the DAPA-HA trial, the CANVAS Program [10] found that canagli ozin signi cantly reduced the risk of cardiovascular death or hospitalization for heart failure in patients with HF concomitant with T2DM.…”
Section: Introductionmentioning
confidence: 74%
“…One study (the CREDENCE trial [13]) was described in an abstract but was eligible and included in this meta-analysis because the complete data were available. All of the studies were randomized, double-blind, placebo-controlled trials (the DECLARE-TIMI 58 trial [9], the CANVAS Program [10], the DAPA-HF trial [11], the EMPA-REG OUTCOME trial [12] and the CREDENCE trial [13]), involving a total of 6945 patients with HF and T2DM. Among the enrolled patients, 4686 (67.5%) were male and 2259 (32.5%) were female.…”
Section: Literature Search Results and Characteristics Of Identi Ed Smentioning
confidence: 99%
See 3 more Smart Citations